articleamssymbemptydocument N = 2document string amplitudes and the Omega background. Issue 9 (5th May 2014) - Florakis, I.; Zein Assi, A.
Abstract: We review recent work [1, 2] on obtaining a realisation of the Ω‐background in terms of a special series of higher‐derivative generalised F‐terms in the effectivearticleamssymbemptydocument N = 2document supergravity action. We discuss the motivation behind the identification of these couplings, their relation to the Nekrasov partition function and connect them to a worldsheet approach towards the refined topological string.